2011
DOI: 10.1002/jso.22046
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of educational video improves patient understanding of basic breast cancer concepts in an undereducated county hospital population

Abstract: Implementation of an educational video significantly improved understanding of breast cancer concepts in an undereducated population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
2
21
0
1
Order By: Relevance
“…A study on the implementation of videos for patients with breast cancer undergoing surgery showed that those who viewed educational videos, despite low education levels, lack of insurance, unemployment, and cultural diversity, were still able to score Ͼ80% on questionnaires. 40 When constructing these videos, one should also tailor the message to patients by including an introduction addressing the purpose of the video and how it can personally assist in their decision-making processes. 41 5) Further- more, the use of stories and pictures, which are often more memorable than statistics and recommendations, can help alleviate patient fears and address their emotional states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on the implementation of videos for patients with breast cancer undergoing surgery showed that those who viewed educational videos, despite low education levels, lack of insurance, unemployment, and cultural diversity, were still able to score Ͼ80% on questionnaires. 40 When constructing these videos, one should also tailor the message to patients by including an introduction addressing the purpose of the video and how it can personally assist in their decision-making processes. 41 5) Further- more, the use of stories and pictures, which are often more memorable than statistics and recommendations, can help alleviate patient fears and address their emotional states.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most important, as mentioned above, the use of images and videos can enhance the material and likely improve the reader's comprehension. [40][41][42] The impact of multimedia needs to be further studied to determine its impact on patients. Additionally, terminology related to neuroradiology is often complex.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous research that has shown improvement in knowledge when a video is used as an educational tool. 1821 Furthermore, the video used in our study was transcreated rather than translated with voiceover. Transcreation has been shown to be more effective than translation in educating Hispanics because it considers both the language and culture of the target population 8, 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding usability of online health information, it can be improved by making changes to the format and design of websites. The changes include the following: (1) using bold type to emphasize major terms and categories; (2) using a font size between 12 and 14 points; (3) avoiding all capital letters, italics, and nontraditional fonts; (4) avoiding the use of medical terms that are not necessary; and (5) actively using videos, stories, and pictures . Usability on mobile devices can be improved by applying a paging format to webpages.…”
Section: Problems and Possible Solutionsmentioning
confidence: 99%
“…The changes include the following: (1) using bold type to emphasize major terms and categories 23 ; (2) using a font size between 12 and 14 points 24 ; (3) avoiding all capital letters, italics, and nontraditional fonts 24 ; (4) avoiding the use of medical terms that are not necessary 25 ; and (5) actively using videos, stories, and pictures. [26][27][28][29] Usability on mobile devices can be improved by applying a paging format to webpages. Previous studies have shown that Web contents presented in a paging format were read faster than in a scrolling format, and comprehension of the contents on a small screen was improved with a paging format.…”
Section: Problems and Possible Solutionsmentioning
confidence: 99%